The Savings Challenge: A Step-by-Step Guide to Financial Empowerment - Junaidi, Ahmad; Lestari, Fransiska Wahyu; Oktoriza, Linda Ayu (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research explores the factors contributing to financial empowerment among customers at Bank DKI KCU Balaikota, focusing on the relationships among Savings Habits (SH), Financial Knowledge (FK), Budgeting Skills (BS), and Financial Empowerment (FE). The study employs a quantitative research design with a random sample of 80 customers, using structural equation modeling with Smart PLS to analyze both direct and indirect effects. The direct effects analysis reveals that Budgeting Skills have a significant positive impact on Financial Empowerment, indicating that individuals with stronger budgeting skills tend to feel more in control of their finances. Similarly, Financial Knowledge is also significantly associated with Financial Empowerment, suggesting that an understanding of financial concepts plays a key role in fostering a sense of financial security. However, the direct path from Savings Habits to Financial Empowerment is not significant, indicating that other factors might influence this relationship. The indirect effects analysis finds that Budgeting Skills significantly mediate the relationship between Savings Habits and Financial Empowerment, emphasizing the importance of effective budgeting as a link between consistent saving and financial control. In contrast, the indirect effect from Financial Knowledge through Budgeting Skills to Financial Empowerment is not significant, suggesting the need for additional factors or direct interventions to bridge this gap. Overall, this study underscores the importance of promoting budgeting skills and financial education as key elements in fostering financial empowerment. The findings have implications for financial institutions and educators, pointing toward a more holistic approach to empowering customers, ultimately leading to greater financial stability and independence.